Low-Dose Triple Antihypertensive Combination Therapy in Patients with Hypertension: A Randomized, Double-Blind, Phase II Study [Corrigendum] - Hong SJ; Sung KC; Lim SW; Kim SY; Kim W; Shin J; Park S; Kim HY; Rhee MY (Dove Medical Press, 2021)
Hong SJ, Sung KC, Lim SW, et al. Drug Des Devel Ther. 2020;14:5735–5746 Page 5735, the affiliation for Ki-Chul Sung should be “2Department of Cardiology, Kangbuk Samsung Hospital, Sungkyunkwan University College of Medicine, Seoul, Republic of Korea”. Page 5744, Acknowledgment section, 4th-6th lines, “....Hospital, Korea University College of Medicine), Ki- Chul Sung (Gangbuk Samsung Hospital, Sungkyunkwan University College of Medicine), Sang-Wook Lim (CHA.....” should read “......Hospital, Korea University College of Medicine), Ki- Chul Sung (Kangbuk Samsung Hospital, Sungkyunkwan University College of Medicine), Sang-Wook Lim (CHA......” The authors apologize for these errors.   Read the original article